Unravelling virulence activities of hospital isolated acinetobacter baumannii: exploring the prospective application of aspirin as an antivirulence agent - Nurrul Syairah A Shukor; Khalida Khalil; Ramliza Ramli; Wan Syaidatul Aqma (Penerbit Universiti Kebangsaan Malaysia, 2024)
Acinetobacter baumannii infections pose a global public health threat due to the increasing resistance to various antimicrobial agents. This study reports the virulence characteristics of A. baumannii strains isolated from patients at Hospital Canselor Tuanku Muhriz UKM (HCTM) and explores the potential of aspirin as an antivirulence agent. Fourteen A. baumannii isolates from various infection sites exhibited resistance to at least two antibiotics. Among them, 43% (n=6) displayed high motility, correlating with the site of isolation. Additionally, 58% (n=7) formed strong biofilms, 36% (n=5) secreted proteases and 36% (n=5) resisted oxidative stress. Notably, isolates Ab_H4 and Ab_H10 displayed the highest virulence, warranting further investigation. Molecular analysis using polymerase chain reaction (PCR) showed that both Ab_H4 and Ab_H10 possessed the bap and katG genes. Although both strains were capable of secreting proteases, only Ab_H4 possessed the cpaA gene, suggesting the involvement of other genes in protease secretion in Ab_H10. Despite high motility, no pilT gene was detected in any isolates. Treatment with sub-inhibitory concentrations of aspirin (3.25 mg/ml) restored susceptibility to previously resistant antibiotics, disrupted biofilm formation, and reduced proteases and catalases secretion. However, no significant impact on bacterial motility was observed. Interestingly, sub-inhibitory concentrations of aspirin induced biofilm formation in the environmental strain control (Ab_UKMCC), which was significantly reduced upon exposure to the MIC. These findings highlight the high virulence capabilities of several strains isolated from HCTM and show the potential of aspirin as an antivirulence agent, offering valuable insights for combating A. baumannii infections.